Adaptive H-infinity tracking control for microgyroscope. (June 2020) - Fang, Yunmei; An, Cuicui; Juan, Wanru; Fei, Juntao
An adaptive H-infinity tracking control is proposed for a z-axis microgyroscope with system nonlinearities. All the signals can be guaranteed in a bounded range, and tracking error is uniformly ultimately bounded, an H-infinity tracking performance is also achieved to a prescribed level. Adaptive control methodology is integrated with H-infinity control technique to achieve robust adaptive control, and adaptive algorithm is used to estimate the unknown system parameters. Simulation studies for microgyroscope are conducted to prove the validity of the proposed control scheme with good performance and robustness.